Computational Study of Flow and Heat Transfer in a Sudden Expansion Channel with Inclined Obstacles (University of Thi-Qar Journal for Engineering Sciences, 2015)
The laminar flow through an obstacled sudden expansion channel is numerically investigated.Rectangular adiabatic inclined obstacles mounted behind the expansion region on the upper and lower wall of the channel were used. The effects of obstacles inclination angle, obstacles length, obstacles thickness and the number of obstacles on the flow and thermal fields for different Reynolds number and expansion ratio were examined. The angle of obstacles inclination was taken in the direction of stream wise flow and ranged from 30° to 90°. Three values of expansion ratio(ER=H/h) equal to 1.5, 1.75 and 2 were used. The choice of values of Reynolds number takes the consideration of symmetry state. The body fitted coordinates system is used to transfer the considered physical problem to computational domain in order to treat the complexity arising from applicable the boundary conditions near the inclined obstacles. The governing stream-vorticity equations expressed in generalized coordinates system were transformed to algebraic equations by using finite difference method. The solution of these equations was done by iteration method. The obtained results showed that there is a significant effect of obstacles angle on the hydrodynamic characteristics. The performed tests of the present results with related published results showed that there is an acceptable agreement.